In-vivo demonstration of the suitability of piezoelectric stimuli for bone reparation - Ribeiro, Clarisse (2017)
he potential of piezoelectric biomaterials for bone tissue engineering is demonstrated. This work proves that the use of piezoelectric poly(vinylidene fluoride) (PVDF), able to provide electrical stimuli upon mechanical solicitation to the growing cells, enhances bone regeneration in vivo. Poled and non-poled β-PVDF films and randomly oriented electrospun fiber mats have been used to test their osteogenic properties in Wistar rats by analyzing new bone formation in vivo. After 4 weeks, defect implanted with poled β-PVDF films demonstrated significantly more defect closure and bone remodeling, showing the large potential of piezoelectric biomaterials for bone repair.